A Low Background Gamma Ray Spectrometer with Anticosmic Shielding - Hung, Nguyen Quoc; Hai, Vo Hong; Tuyet, Tran Kim; Tuan, Ho Lai (Communications in Physics, 2016)
The article describes a gamma ray spectrometer protected by a lead shield (Model 747E Canberra lead shield) and an active shield made of an 80 cm \(×\) 80 cm \(×\) 3 cm plastic scintillator plate in anticoincidence on top of the lead shield. The detector used as low background gamma-spectrometer is a high purity Germanium crystal of model GC2018 Canberra. The background count rate currently achieved (30-2400 keV) is 1.27 cps without anticoincidence. The level of background suppression obtained from the active protection is 0.80 overall and about 0.43 for the 511 keV gamma line. The gamma ray spectrometer is installed and operated in the Nuclear Laboratory, Department of Nuclear Physics, University of Science, HCMC-Vietnam National University